The Italian Verb : A Morphological Study - Jensen, Frede, 1926- (Book collections on Project MUSE., 1971)
This morphological study is designed to show the transformation from Latin verbs into the Old and Modern Italian verbal system. The work is inspired by the methods of traditional, historical philology, and its intent is largely pedagogical.